2017
DOI: 10.12932/ap0820
|View full text |Cite
|
Sign up to set email alerts
|

Component-resolved diagnostics in Thai children with cow’s milk and egg allergy

Abstract: BLG and casein for cow's milk and ovomucoid and ovalbumin for egg were the common components causing sensitization in cow's milk and egg allergic patients. Among the patients with cow's milk allergy, the level of casein sIgE in the urticaria group tended to be higher than the AD group, and in egg allergic patients, the non-AD group had a significantly higher ovomucoid sIgE level compared with the AD group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…34,55 Studies on the sensitivity profiles of Thai children with CMA indicate that most were sensitive to βLG and casein. 72 Similarly, a Japanese study found that 97% of children with these demonstrate sensitivity of 63 and 61% and specificity of 87 and 83%, respectively. No other milk components were found to give clinically relevant results.…”
Section: Casein Proteinsmentioning
confidence: 94%
See 2 more Smart Citations
“…34,55 Studies on the sensitivity profiles of Thai children with CMA indicate that most were sensitive to βLG and casein. 72 Similarly, a Japanese study found that 97% of children with these demonstrate sensitivity of 63 and 61% and specificity of 87 and 83%, respectively. No other milk components were found to give clinically relevant results.…”
Section: Casein Proteinsmentioning
confidence: 94%
“…Another example of the use of CRD in determining the phenotype of the disease may be that given by Jessadapakorn et al, 72 in which higher casein levels were observed in children with urticaria compared to children CMA who acquired tolerance before the age of four compared to healthy children. Instead, they showed that high levels of milk components and milk sIgE increase the risk of long-lasting or persistent CMA.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of crude allergen extracts reduces the reliability of those tests since they often contain a mixture of allergenic and nonallergenic components. The difficulties associated with crude allergen extracts can be easily overcome by the use of component-resolved diagnosis (CRD) [ 7 ]. In CRD, specific allergens are used for measurement of sIgE [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study of children with CMA showed that the positive rates of β-lactoglobulin and casein were the highest, followed by a-lactalbumin. [ 10 ] Therefore, β-lactoglobulin might be a more sensitive indicator of CMA.…”
mentioning
confidence: 99%